Comparison of different detection methods for Mycoplasma pneumoniae infection in children with community-acquired pneumonia - Mingyu Tang; Dong Wang; Xing Tong; Yufen Wu; Jing Zhang; Lei Zhang; Yong Yin; Qing Cao (BMC, 2021)
Abstract Background Due to the lack of a sensitive, specific and rapid detection method, aetiological diagnosis of pneumonia caused by Mycoplasma pneumoniae (M. pneumoniae, MP) is a constantly challenging issue. This retrospective study aimed to compare the diagnostic methods for Mycoplasma pneumoniae in children and evaluate their values. Methods From November 2018 to June 2019, 830 children with community-acquired pneumonia were selected from the Department of Respiratory Medicine, Shanghai Children's Medical Center. On the first day of hospitalization, sputum, throat swab and venous blood samples were collected to analyse MP-IgM (particle agglutination, PA), MP-IgM (immune colloidal gold technique, GICT), MP-DNA, MP-RNA (simultaneous amplification and testing, SAT) and MP-DNA (real-time polymerase chain reaction, RT-PCR). Results Among these 830 children, RT-PCR showed that the positive rate was 36.6% (304/830), in which the positive rate of macrolide resistance (A2063G mutation) accounted for 86.2% of cases (262/304). Using RT-PCR as the standard, MP-RNA (SAT) had the highest specificity (97.5%), and MP-IgM (PA) had the highest sensitivity (74.0%) and Youden index (53.7%). If MP-RNA (SAT) was combined with MP-IgM (PA), its Kappa value (0.602), sensitivity (84.2%), specificity (78.7%) and Youden index (62.9%) were higher than those of single M. pneumoniae detection. Conclusions Our research indicated that a combination of MP-RNA (SAT) plus MP-IgM (PA) might lead to reliable results as an early diagnostic method for children with clinical manifestations of Mycoplasma pneumoniae pneumonia.